Rola świadectwa w rodzinie - Goleń, Jacek (Verbum Vitae, 2015)
True humanness reaches its fulfillment in Christ. It is faith that enables one to appreciate fully that gift of humanness, its value and its meaning, as well as to realize the marital-familial vocation. Testimony given to Christ in the Christian family takes on a more visible form as it harmonizes with the mature testimony of humanness. An important role of testimony in the family expresses itself in the objectives of this testimony. The testimony of humanness expresses itself in the task of building a community of persons and lasting marriage, respect towards persons and the human body, and commitment to maturing love and the realization of parenthood. Testimony of faith is connected with the task of professing God’s Word, realization of one’s baptismal priesthood, love and apostolate. Sacramental grace and prayer enable spouses and other family members to fully discover and realize these tasks.